2010
DOI: 10.2478/v10042-010-0011-5
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between metallothionein (MT) expression and selected prognostic factors in ductal breast cancers.

Abstract: Abstract:Our study aimed at examining significance of metallothionein (MT) expression in ductal breast cancers by determination of a relationship between expression of MT protein (MT-1/2) and selected prognostic factors, including grade of histological differentiation (G), expression of Ki-67 proliferative antigen, expression of estrogen receptors (ER) and progesterone receptors (PgR) and expression of HER-2 receptor. Material for the studies involved 54 samples of invasive ductal breast cancer, manifesting ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 41 publications
3
25
0
1
Order By: Relevance
“…Therefore, the reduced expression of MT1 and MT2 might result in the increased cardiomyocyte apoptosis in STAT3cKO hearts with decreased resistance against ROS. In addition to cytoprotection, it is also reported that the expression of MTs is positively associated with cell proliferation particularly in malignancies 4548 , possibly though the maintenance of zinc homeostasis 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the reduced expression of MT1 and MT2 might result in the increased cardiomyocyte apoptosis in STAT3cKO hearts with decreased resistance against ROS. In addition to cytoprotection, it is also reported that the expression of MTs is positively associated with cell proliferation particularly in malignancies 4548 , possibly though the maintenance of zinc homeostasis 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Expression of estrogen (ER) and progesterone (PR) receptors were conducted according to the earlier described procedure [27]. The sections were deparaffinized and rehydrated in Antigen Retrieval Solution (pH 6; Dako).…”
Section: Methodsmentioning
confidence: 99%
“…Most work is focused on the immunohistochemical determination of MTs in tumors Babula et al, 2011;Eckschlager et al, 2009;Gumulec et al, 2011;Krizkova et al, 2008Krizkova et al, , 2009Krizkova et al, , 2010Krizkova et al, , 2012Sochor et al, 2012), but also on its determination in serum by various methods, such as Brdicka's reaction or enzymelinked immonosorbent assay Krizkova et al, 2010). MT can serve as a prognostic marker in central nervous system tumors of childhood and adolescence (Rickert and Paulus, 2005;Rickert, 2004), osteosarcoma (Trieb and Kotz, 2001), breast cancer (Woolston et al, 2010;Jin et al, 2004;Gomulkiewicz et al, 2010), pancreatic islet cell tumors (Tomita, 2002), and tongue squamous-cell carcinoma (Theocharis et al, 2011). MT can also serve as a serum tumor marker in prostate cancer Masarik et al, 2011), head and neck tumors , childhood solid tumors , and melanoma .…”
Section: Mts In Cancer Diagnosismentioning
confidence: 99%